Edukasi UU ITE untuk Generasi Z di SMAN 1 Surakarta: Memahami Hak-Hak Bermedia Sosial dan Verifikasi Latar Belakang Saat Melamar Pekerjaan - Sutoyo Sutoyo; Apri Winge A (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to examine the understanding of students of SMAN 1 Surakarta towards the Electronic Information and Transaction Law (UU ITE), especially in the aspect of social media rights and the importance of background verification when applying for a job. This study used a qualitative approach with interview and participatory observation methods. The results showed that although students have basic knowledge of the prohibitions in ITE Law, their understanding of specific articles and legal consequences is still low. Formal education on ITE Law has not been optimally integrated in the school curriculum, so students obtain information from the media or personal experience. When it comes to verifying information when applying for a job, students tend to focus on the technical aspects, with no awareness of the importance of building a digital reputation. These findings underscore the need for educational approaches that are contextualized and based on students' digital experiences, such as case study-based learning and collaboration with legal practitioners. This research contributes to the development of digital law learning designs that are responsive to the needs of Generation Z and opens up opportunities for further research on digital legal literacy at the secondary education level.